Electronic Word-of-Mouth (e-WOM): A Bibliometric Mapping of Scientific Literature - Loso Judijanto; Sintia Permata Sari; Tina Isnaeni (Westscience Press, 2026)
With the rise of importance of digital platform use, social media interaction and online consumer activities in decision-making and brand perception processes, Electronic Word-of-Mouth (e-WOM) becomes one of the active fields for scholarly investigations. In order to study the intellectual structure, research development and trends in e-WOM literature, the present study used a bibliometric analysis method. The data was gathered from academic database entries of scientific publications and were analyzed using bibliometric methods, such as citation analysis, co-authorship analysis, keyword co-occurrence analysis, thematic mapping and trends analysis. It was found out that the research on e-WOM was gradually shifting from the issues of consumer motivation, online reviews, and credibility of information towards more general issues like social media, user generated content, purchase intention, brand image and digital consumer behavior. Citation analysis allows identifying fundamental research papers that shaped this field to a great extent, especially in terms of e-WOM adoption, credibility and consumer involvement in it. The cooperation analysis shows that despite the global development of e-WOM research, the fragmentation of authorship, institutionality and inter-country collaboration still exists. Additionally, the thematic evolution proves that modern researches in the area of e-WOM is gradually shifting towards the issues of digital platforms, social media marketing, sentiment analysis and data-driven consumer insights. The present study provides a comprehensive look into the evolution and knowledge base of e-WOM research and defines the possible directions of future research related to artificial intelligence, influencer communication, recommendation algorithms and digital trust.